Climate-smart agriculture measurement, reporting and verification in the Republic of Malawi - World Agroforestry Centre; Unique Forestry and Land Use (2019)
Agriculture is critical to Malawi’s future. It accounts for 80% of employment, more than 80% of foreign exchange earnings, and 64% of total income among the rural population. Due to the importance of agriculture to livelihoods and the economy, Malawi is among the countries most at risk from climate change and variability. Climate-smart agriculture (CSA) has been proposed as one solution for Malawi, and the country’s first CSA programme was initiated in 2014. However, outcomes from activities specifically identified as CSA or projects with similar goals have not yet been tracked or reported on. The consequence is that the contribution of these actions to the achievement of national development and climate goals are not accounted for, and CSA is not explicitly integrated into budgetary processes or being used to leverage additional investments in rural development and climate resilience.